2021
DOI: 10.3389/fnmol.2021.767842
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Dendritic Synaptic Morphology and Transcription by the SRF Cofactor MKL/MRTF

Abstract: Accumulating evidence suggests that the serum response factor (SRF) cofactor megakaryoblastic leukemia (MKL)/myocardin-related transcription factor (MRTF) has critical roles in many physiological and pathological processes in various cell types. MKL/MRTF molecules comprise MKL1/MRTFA and MKL2/MRTFB, which possess actin-binding motifs at the N-terminus, and SRF-binding domains and a transcriptional activation domain (TAD) at the C-terminus. Several studies have reported that, in association with actin rearrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…1,2) MKL/MRTF is abundant in the brain and regulates the morphology of dendrites and synapses. 3,4,5,6) MKL/MRTF double KO in the brain revealed a phenotype that was similar to that of SRF KO in the brain. 7) We previously isolated various MKL1/MRTFA and MKL2/MRTFB isoforms and found that their mRNA expression patterns were different during brain development.…”
Section: Introductionmentioning
confidence: 66%
“…1,2) MKL/MRTF is abundant in the brain and regulates the morphology of dendrites and synapses. 3,4,5,6) MKL/MRTF double KO in the brain revealed a phenotype that was similar to that of SRF KO in the brain. 7) We previously isolated various MKL1/MRTFA and MKL2/MRTFB isoforms and found that their mRNA expression patterns were different during brain development.…”
Section: Introductionmentioning
confidence: 66%
“…This lack of regulation by Actin appears to be the key to several of the phenotypes observed in the probands, possibly including the neurological phenotypes. As evidenced by mouse and rat models, proper MRTFB/SRF activity is important for the production of dendritic spines, establishing proper dendritic complexity, and assembling neural circuits 4 . While additional research is necessary to demonstrate if and how MRTFB R104G and MRTFB A91P affect neurological development, it is plausible that the lack of regulation present in these alleles may be sufficient to alter normal patterns of neuronal growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardin-Related Transcription Factor B (MRTFB) is one of three members of the myocardin family [1][2][3] , a group of transcription factors known to contribute to proper cardiac development, smooth muscle differentiation, and the regulation of synaptic morphology [4][5][6][7][8][9][10][11] . The three members of this family, MYOCD, MRTFA and MRTFB, are located at different chromosomal loci but share several distinct structural features, including an N-terminal domain, a basic region, a B-box-like region, a glutamine-rich region, a SAP domain, a leucine zipper and a transcription activation domain 1,[12][13][14] (FIG.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular binding of actin fibers contributes to the nature and structure of scaffolding proteins, and thus to the extracellular tethering of neurotransmitters to their specific receptors, a process of great relevance in the regulation of synaptic gating [ 17 , 19 ]. Both positive and negative controls of these effects are mediated by serum response factors (SRFs), abundant in the synaptic areas together with its MKL/MRTF cofactor [ 20 ]. Microtubules, operative from their specific cytoskeleton, are important for both the composition and orientation of dendritic fibers and synapses.…”
Section: Flat/intended/aspine Post-synapsesmentioning
confidence: 99%